Penerapan Model Pembelajaran Kooperatif Student Team Achievement Division (STAD) Berbantuan Kahoot untuk Meningkatkan Keaktifan Belajar Siswa Kelas XI SMA Al Islam 1 Surakarta - Aisyah Nurul Izzah (Departement of Mathematics Education, 2023)
This research is a type of Classroom Action Research (CAR). This research lasted two cycles. Each cycle consists of 4 stages, namely planning, action, observation, and reflection. The research subjects were students of class XI SMA Al Islam 1 Surakarta. Data collection techniques through observation, interviews, and documentation. The results showed that through the application of the Kahoot-assisted Student Team Achievement Division (STAD) cooperative learning model, it was possible to increase the activeness of student learning from pre-action, cycle I and cycle II. This was proven during the pre-action the percentage of student learning activeness was 31.57%. In cycle I the application of the Kahoot-assisted Student Team Achievement Division (STAD) cooperative learning model increased student activity with a percentage of 47.36%, then in cycle II there was an increase in the percentage of student learning activeness of 78.94%. Conclusion Classroom Action Research (PTK) by applying the Kahoot-assisted Student Team Achievement Division (STAD) cooperative learning model can increase the learning activity of class XI students at SMA Al Islam 1 Surakarta.